Determinants of sleep quality among pregnant women in China: a cross-sectional survey. (17th November 2018) - Yang, Ying; Mao, Jing; Ye, Zhiying; Zeng, Xiaoli; Zhao, Huimin; Liu, Yueting; Li, Jie
Abstract: Purpose: Sleep disturbances are common during pregnancy, yet few studies are currently available regarding the determinants of sleep quality among pregnant women in China. This study aimed to: (a) calculate the prevalence of sleep disorder during pregnancy, (b) examine the difference in sleep quality among three trimesters, and (c) identify determinants of sleep quality in pregnant women. Materials and methods: This study was designed as a cross-sectional survey. Five hundred pregnant women were recruited at the outpatient department of obstetrics and gynecology of two teaching hospitals in central China. Five selfreport questionnaires were used for gathering data, including information of sample characteristics, sleep quality (Pittsburgh Sleep Quality Index (PSQI)), prenatal depression (the Edinburgh Postnatal Depression Scale (EPDS)), perceived stress (Perceived Stress Scale (PSS)), and perceived social support (Multidimensional Scale of Perceived Social Support (MSPSS)). Results: A total of 454 pregnant women participated in the study between September 2016 and April 2017. Eighty-seven percent pregnant women experienced sleep disorder (PSQI score >5). Poorer global sleep quality, subjective sleep quality, lower sleep efficiency and sleep disturbances were most prevalent during third trimester. The significant contributors to sleep quality for pregnant women were prenatal depression, maternal age, and gestational age. Conclusions: Sleep disorder is very common in pregnant women from China. Depressive symptoms, increased maternal age, and gestational age are determinants of sleep quality. These determinants can assist healthcare professionals in preventative intervention.